Menstrual phase influences cerebrovascular responsiveness in females but may not affect sex differences - Skinner, Bethany D.; Weaver, Samuel R. C.; Lucas, Samuel J. E.; Lucas, Rebekah A. I. (Frontiers in Physiology, 2023)
Sex differences in the rate and occurrence of cerebrovascular diseases (e.g., stroke) indicate a role for female sex hormones (i.e., oestrogen and progesterone) in cerebrovascular function and regulation. However, it remains unclear how cerebrovascular function differs between the sexes, and between distinct phases of the menstrual cycle. This study aimed to compare cerebrovascular-CO2 responsiveness in 1) females during the early follicular (EF), ovulatory (O) and mid-luteal (ML) phases of their menstrual cycle; and 2) males compared to females during phases of lower oestrogen (EF) and higher oestrogen (O). Eleven females (25 ± 5 years) complete experimental sessions in the EF (n=11), O (n=9) and ML (n=11) phases of the menstrual cycle. Nine males (22 ± 3 years) completed two experimental sessions, approximately two weeks apart for comparison to females. Middle and posterior cerebral artery velocity (MCAv, PCAv) was measured at rest, during two stages of hypercapnia (2 and 5% CO2 inhalation) and hypocapnia (voluntary hyperventilation to an end-tidal CO2 of 30 and 24mmHg). The linear slope of the cerebral blood velocity response to changes in end-tidal CO2 was calculated to measure cerebrovascular-CO2 responsiveness. In females, MCAv-CO2 responsiveness to hypocapnia was lower during EF (-0.78 ± 0.45 cm/s/mmHg) when compared to the O phase (-1.17 ± 0.52 cm/s/mmHg; p<.05) and the ML phase (-1.30 ± 0.82; p<.05). MCAv-CO2 responsiveness to hypercapnia and hypo-to-hypercapnia, and PCAv-CO2 responsiveness across the CO2 range were similar between menstrual phases (p≥.20). MCAv-CO2 responsiveness to hypo-to-hypercapnia was greater in females compared to males (3.12 ± 0.91 cm/s/mmHg vs. 2.31 ± 0.46 cm/s/mmHg; p=.03), irrespective of menstrual phase (EF or O). In summary, females during O and ML phases have an enhanced vasoconstrictive capacity of the MCA compared to the EF phase. Additionally, biological sex differences can influence cerebrovascular-CO2 responsiveness, dependent on the insonated vessel.